WANPRESTASI PT. NINDYA KARYA (PERSERO) WILAYAH III KEPADA UNIT PENUNJANG PRODUKSI DALAM PERJANJIAN KERJASAMA DI WILAYAH BANDARA SUPADIO PONTIANAK - NIM. A1012191079, AURELLIA SANDRA PUSPITA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac PT. Nindya Karya (Persero) is a State-Owned Enterprise (BUMN) engaged in General Contractor, EPC and Investment which has five main business pillars Construction, Energy, Manufacturing, Property and Toll Road Business Entities. PT. Nindya Karya (Persero) was established on March 11, 1960. This company began its history in 1921 as the Indonesian branch of NV Nederlandsche Aannemings Maatschappij (Nedam). In 1958, the branch was nationalized by the Indonesian government. In 1960, the Ministry of Public Works and Labor changed the name of the branch to the Nindya Karya Building Company. In 1961, the government established this company as a state company (PN) and in 1973, the company's status was changed to Persero. PT. Nindya Karya (Persero) has many branch companies, one of which is in West Kalimantan, Pontianak City, which is included in area III. The lease agreement made between the Plt. Unit Head PT. Nindya Karya (Persero) with the General Manager of PT. Nindya Karya (Persero) Region III in written form.So the author draws a problem formulation as follows: